2021
DOI: 10.1007/s12602-021-09825-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriocins Produced by LAB Isolated from Cheeses within the Period 2009–2021: a Review

Abstract: A survey is presented concerning original research articles published in well-reputed scientific journals on the isolation of lactic acid bacteria (LAB) from cheeses worldwide, where researchers evaluated the bacteriocin production by such isolates in searching for novel functional peptides that can exhibit potential for biotechnological applications. Seventy-one articles were published in the period of study, with contributions being American (45%), Asiatic (28%), and European (21%), being Brazil-USA-Mexico, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 83 publications
(88 reference statements)
0
9
0
2
Order By: Relevance
“…Moreover, it is produced antimicrobial substances such as bacteriocins, BLIS, hydrogen peroxide, organic acids, diacetyl, acetoin, and antifungal peptides (Egan et al, 2016). LAB produce a large number of bacteriocins from strains like Lactobacillus, Pediococcus, Lactococcus, and Enterococcus (Trejo-González et al, 2021).…”
Section: Bacteriocins Of Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…Moreover, it is produced antimicrobial substances such as bacteriocins, BLIS, hydrogen peroxide, organic acids, diacetyl, acetoin, and antifungal peptides (Egan et al, 2016). LAB produce a large number of bacteriocins from strains like Lactobacillus, Pediococcus, Lactococcus, and Enterococcus (Trejo-González et al, 2021).…”
Section: Bacteriocins Of Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…EPSs play a key role in hostmicrobe interactions by helping beneficial microbes to colonize the intestine and by acting as immunomodulators (Caggianiello et al, 2016;Korcz et al, 2018;Oerlemans et al, 2021). Some LAB can produce bacteriocins (Trejo-González et al, 2022); the best known example is nisin, which is a bacteriocin produced by a group of bacteria belonging to the genera Lactococcus and Streptococcus. Nisin is classified as a type A (I) antibiotic synthesized from mRNA, and the translated peptide contains several unusual amino acids due to posttranslational modifications (Shin et al, 2016).…”
Section: Extracellular and Secreted Bioactive Componentsmentioning
confidence: 99%
“…These authors compiled comprehensive information in three tables, available from 2000 to 2018, about the application of purified or semi‐purified bacteriocins and their producing LAB for different dairy products such as raw, UHT and sterilized milk, skimmed milk powder, different varieties of cheeses and some fermented milk including yoghourt (Silva et al, 2018). More recently, Trejo‐González et al (2021) conducted a bibliographic search in different databases for articles (from 2009 to 2021) dealing with bacteriocin‐producing LAB isolated from cheeses. They found that more than 30% of these LAB belong to Enterococcus and (former) Lactobacillus genera, followed by Lactococcus and Pediococcus (less than 14%), which were most often isolated from soft cheeses (Trejo‐González et al, 2021).…”
Section: Cultures For Dairy Safety and Preservationmentioning
confidence: 99%
“…More recently, Trejo‐González et al (2021) conducted a bibliographic search in different databases for articles (from 2009 to 2021) dealing with bacteriocin‐producing LAB isolated from cheeses. They found that more than 30% of these LAB belong to Enterococcus and (former) Lactobacillus genera, followed by Lactococcus and Pediococcus (less than 14%), which were most often isolated from soft cheeses (Trejo‐González et al, 2021). The application of nisin, which is synthesized by Lactococcus , against spore‐forming bacteria in food production was also recently revisited since it is of special relevance for extending the shelf‐life of fermented products (Anumudu et al, 2021).…”
Section: Cultures For Dairy Safety and Preservationmentioning
confidence: 99%